Optimization of temperature and pasteurization time of soursop juice (Annona muricata) by response surface methodology in pilot scale. Issue 1 (November 2021) - Argo, B D; Amaliyah, F A
Abstract: Interest in soursop and its derivatives has increased over time, with many scientific articles reporting its health benefits. Several recent studies reported the presence of bioactive compounds and phytochemicals from soursop juice. However, climatic fruit tends to have different post-harvest handling than others. A series of processes from harvesting to extraction played an important role in its final product. The thermal inactivation of the PPO enzyme, which causes brownish color, can be used to improve the quality of soursop juice. This process can be carried out using the MTLT (Mild Temperature Long Time) pasteurization process using a customized double jacket heater by considering the thermoresistence properties of bioactive compounds in soursop juice. This study aims to determine the optimal formulation for process parameters also provide the optimal choice for the pasteurization process in pilot scale and database for the transition to industrial production. Response Surface Methodology (RSM) was a method used to optimize the process and formulation of soursop fruit juice. In this study, two factors were used, namely pasteurization temperature (56-80 °C) and heating time (5-15 min) obtained by previous research to determine the most optimal total Total Phenolic Content (TPC), Total Flavonoid Content (TFC), Color measurement, Total Dissolve Solid and Viscosity.